Low skeletal muscle mass index is associated with function and nutritional status in residents in a Turkish nursing home. (2nd July 2016) - Tufan, Asli; Bahat, Gulistan; Ozkaya, Hilal; Taşcıoğlu, Didem; Tufan, Fatih; Saka, Bülent; Akin, Sibel; Karan, Mehmet Akif
Abstract: Introduction : To determine the prevalence of low muscle mass (LMM) and the relationship between LMM with functional and nutritional status as defined using the LMM evaluation method of European Working Group on Sarcopenia in Older People (EWGSOP) criteria among male residents in a nursing home. Methods : Male residents aged >60 years of a nursing home located in Turkey were included in our study. Their body mass index (BMI) kg/m 2, skeletal muscle mass (SMM-kg) and skeletal muscle mass index (SMMI-kg/m 2 ) were calculated. The participants were regarded as having low SMMI if they had SMMI <9.2 kg/m 2 according to our population specific cut-off point. Functional status was evaluated with Katz activities of daily living (ADL) and Lawton Instrumental Activities of Daily Living (IADL). Nutritional assessment was performed using the Mini Nutritional Assessment (MNA). The number of drugs taken and chronic diseases were recorded. Results : One hundred fifty-seven male residents were enrolled into the study. Their mean age was 73.1 ± 6.7 years with mean ADL score of 8.9 ± 2.0 and IADL score of 8.7 ± 4.6. One hundred twelve (71%) residents were aged >70 years. Thirty-five men (23%) had low SMMI in group aged >60 years, and twenty-eight subjects (25%) in the group aged >70 years. MNA scores were significantly lower in residents with low SMMI compared with having normal SMMI (17.1 ± 3.4 versus 19.6 ± 2.5, p = 0.005). BMI was significantly lower in the residents with low SMMI compared with normal SMMI (19.6 ± 2.7 versus 27.1 ± 4.1, p < 0.001). ADL scores were significantly different between residents with low SMMI and normal SMMI in those aged >70 years (8.1 ± 2.6 versus 9.1 ± 1.6, p = 0.014). In regression analyses, the only factor associated with better functional status was the lower age ( p = 0.04) while the only factor associated with better nutrition was higher SMMI ( p = 0.01). Conclusions : Low SMMI detected by LMM evaluation method of EWGSOP criteria is prevalent among male nursing home residents. There is association of low SMMI with nutritional status and probably with functional status within the nursing home setting using the EWGSOP criteria with Turkish normative reference cut-off value.